Stigma towards non-suicidal self-harm: evaluating a brief educational intervention. (14th March 2019) - Gibson, Rebecca; Carson, Jerome; Houghton, Trish
Abstract : Background: health professionals' attitudes towards self-harming behaviour are predominantly negative. Research examining educational interventions to change negative attitudes is limited. Aims: this study aimed to provide an educational intervention for student nurses to change negative attitudes around self-harm. Methods: attitudes around self-harm and mental health in general were assessed through the Self-Harm Antipathy Scale and the Mental Health Attitude Scale. Fifty-five adult nursing students took part in the 45–minute intervention. This included facts and figures, celebrity stories and personal stories regarding self-harm, all intended to increase understanding. Findings: after the intervention, attitudes measured by the Self-Harm Antipathy Scale had improved significantly. Conclusion: patients who self-harm will without doubt continue to experience negative attitudes from health professionals. This study shows an educational intervention can change attitudes towards those who self-harm.